Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.

De novo structure prediction of meteorin and meteorin-like protein for identification of domains, functional receptor binding regions, and their high-risk missense variants - Shankar, S. Shiva; Banarjee, Reema; Jathar, Swaraj M.; Rajesh, S.; Ramasamy, Sureshkumar; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2024)
Meteorin (Metrn) and Meteorin-like (Metrnl) are homologous secreted proteins involved in neural development and metabolic regulation. In this study, we have performed de novo structure prediction and analysis of both Metrn and Metrnl using Alphafold2 (AF2) and RoseTTAfold (RF). Based on the domain and structural homology analysis of the predicted structures, we have identified that these proteins are composed of two functional domains, a CUB domain and an NTR domain, connected by a hinge/loop region. We have identified the receptor binding regions of Metrn and Metrnl using the machine-learning tools ScanNet and Masif. These were further validated by docking Metrnl with its reported KIT receptor, thus establishing the role of each domain in the receptor interaction. Also, we have studied the effect of non-synonymous SNPs on the structure and function of these proteins using an array of bioinformatics tools and selected 16 missense variants in Metrn and 10 in Metrnl that can affect the protein stability. This is the first study to comprehensively characterize the functional domains of Metrn and Metrnl at their structural level and identify the functional domains, and protein binding regions. This study also highlights the interaction mechanism of the KIT receptor and Metrnl. The predicted deleterious SNPs will allow further understanding of the role of these variants in modulating the plasma levels of these proteins in disease conditions such as diabetes.
Keywords: domains; Meteorin; meteorin-like; missense variants; protein-protein interactions; structure prediction

Characterization of S-homocysteinylation of Human Insulin and Its Implications in Diabetes - Sheikh, Amreen B.; Jathar, Swaraj M.; Tammara, Vaishnavi; Das, Atanu; Kulkarni, Mahesh J. (Protein Journal, 2025)
Homocysteine thiolactone is a reactive thiol known for its interaction with various proteins. Nevertheless, there exists a paucity of information concerning the interaction between homocysteine thiolactone and human insulin, particularly regarding the mechanism by which homocysteine facilitates the reduction of disulfide bonds within insulin. In the present study, we have elucidated the binding sites of homocysteine to the cysteine residues (A6-B7 and A20-B19) that are implicated in the formation of intermolecular disulfide bonds in insulin through an in vitro reaction analyzed via LC-ESI MS/MS. This results in a reduction of disulfide bonds linking the A and B chains, which was corroborated by MALDI-TOF-MS and ESI-MS analysis. The secondary structure of insulin is affected by this modification, as evidenced by circular dichroism spectroscopy. In-silico studies also show that homocysteine affects the insulin structure. A glucose uptake assay conducted in Chinese hamster ovary (CHO) cells that stably express the insulin receptor revealed that HC-modified insulin is less effective in inducing glucose uptake compared to native insulin, suggesting that HC-induced structural modifications in insulin influence functional activity. This study provides insight into the HC-induced structural and functional changes in insulin and discusses the consequent implications for diabetes.
Keywords: Disulfide bonds; Homocysteinylation; insulin; Mass spectrometry